Soil water balance in the Lake Chad Basin using stable water isotopes and chloride of soil profiles. Issue 5 (3rd September 2019) - Tewolde, Daniel Okubay; Koeniger, Paul; Beyer, Matthias; Neukum, Christoph; Gröschke, Maike; Ronelngar, Melanie; Rieckh, Helene; Vassolo, Sara
ABSTRACT: The Lake Chad Basin (LCB) is an endorheic transboundary catchment highly vulnerable to drought. For effective groundwater management, recharge areas need identification and replenishment quantification. At present, little research exploring unsaturated zone water flow processes and groundwater recharge are available. In this study, 12 vertical soil profiles were analysed for stable water isotopes and chloride concentration to estimate evaporation and groundwater renewal. Most δ 18 O and δ 2 H isotope profiles reveal typical arid environment patterns, with maximum enrichment at depths between 2.5 and 20 cm and depletion towards the surface (atmospheric influence) and depth (mixing and diffusion). Average annual dry season evaporation rates in Salamat and Waza Logone range from 5 to 30 mm, in Bahr el Ghazal and Northern Lake Chad from 14 to 23 mm. According to the chloride mass balance (CMB), the average annual recharge rate is estimated between 3 and 163 mm in Salamat and Waza Logone and less than 1 mm in Bahr el Ghazal and Northern Lake Chad. Based on the CMB results, potential recharge sites were identified, while estimated soil evaporation corresponds to plant water use at the initial growing stage, which is an important component in irrigation water management.